PATH-46. DETECTING MISDIAGNOSED ATYPICAL TERATOID/RHABDOID TUMOR (ATRT) BY DNA METHYLATION-BASED TUMOR CLASSIFICATION. (11th November 2019) - Hsiao, Meng-Chang; Holinka, Lauren; Peracchio, Michael; Kelly, Kevin; Hesse, Andrew; Lau, Ching; Reddi, Honey
Abstract: Brain tumor diagnostics is achieved by combining morphology assessment and biomarker identification. However, the inter-observer variability of the histopathological diagnosis and lack of distinctive biomarkers makes these diagnoses particularly challenging. Recently, the potential for methylation-based characterization has been developed for brain tumors. To provide accurate and efficient brain tumor diagnostics, The Jackson Laboratory developed a DNA methylation array (Illumina Infinium HD Methylation EPIC), combining the "Classifier" established by the German Cancer Research Center (DKFZ), which can identify 82 distinct central nervous system tumors. Here we present a pediatric patient referred to us for medulloblastoma subtype classification by the methylation profile. Surprisingly, the array classified the tumor type as atypical teratoid/rhabdoid tumor (ATRT), subclass SHH. Also, the CNV profile indicated the SMARCB1/INI1 heterozygous deletion as part of the chromosome 22q deletion typically seen in ATRT, and absent was the isochromosome 17q commonly associated with medulloblastoma. Immunohistochemistry confirmed the loss of SMARCB1/INI1 expression leading to ATRT. Additionally, our NGS panel found a novel SMARCB1/INI1 frameshift variant c.1150delG (p.Ala384fs) in the last exon (exon 9). Although this variant is not expected to induce nonsense-mediated mRNA decay, it is located in the ATP-dependent nucleosome-remodeling complex domain Sfh1/SNF5 (IPR017393), which is associated with cell proliferation and differentiation. In addition, ClinVar reported several pathogenic/likely pathogenic variants in this domain, further supporting SMARCB1/INI1 c.1150delG which, together with the SMARCB1/INI1 deletion, may contribute to the loss of SMARCB1/INI1 expression, resulting in ATRT. We have identified the ATRT misclassification by the methylation profile and characterized a novel SMARCB1/INI1 variant c.1150delG most likely contributing to ATRT. We further propose that the DNA methylation profile will significantly improve the brain tumor diagnostics for cases with ambiguous, or contradictory histology and molecular profiles.